Emergency department nurses experiences of female domestic violence presentations: A review of the qualitative literature. Issue 4 (4th August 2021) - Christensen, Martin; Metcalfe, Lauren‐Leigh; O'Reilly, Rebecca
Abstract: Domestic violence (DV) is a prominent social problem involving upwards of 30% of women and in most cases, it is often the emergency department (ED) that is the first point of call. This qualitative review aimed to explore and describe ED nurses experiences of DV presentations. A search of the qualitative literature was undertaken between 2000 and 2019. This review was performed using a three‐stage process of thematic synthesis. For papers to be included each paper must have described a qualitative account of ED nurses' experiences of DV presentations. Ten papers met the inclusion criteria. Three themes emerged from the papers reviewed—feeling devastated in a world of helplessness and hopelessness; the anger of indifference; and grieving the pain and suffering. These included feelings of anger, rage, depression, guilt, helplessness, sadness, hopelessness, and cynicism. In conclusion, the emotional burden of care in supporting and protecting victims of DV can be immense for the nurses involved. This can lead to ED nurses distancing themselves from the patient as a means of emotional self‐protection as well as increasing compassion fatigue as a result of secondary vicarious trauma.